Changes in facial emotion expression during a psychotherapeutic intervention for patients with borderline personality disorder. (July 2019) - Arango, Iván; Miranda, Edgar; Sánchez Ferrer, José Carlos; Fresán, Ana; Reyes Ortega, Michel A.; Vargas, Angélica Nathalia; Barragán, Sandra; Villanueva-Valle, Javier; Munoz-Delgado, Jairo; Robles, Rebeca
Abstract: Emotional dysregulation is one of the main features of Borderline Personality Disorder (BPD). Therefore, it constitutes a central therapeutic objective of the interventions that have proven to be effective for these patients, including the Acceptance and Commitment Therapy (ACT). However, benefits on emotional regulation have been evaluated through self-report instruments, and an anatomically based, objective, and precise measurement of the ability to change the type, duration and frequency of emotions is still needed. Objective: To assess facial emotion expression, valence and arousal during an ACT based intervention, between initial, middle and final therapeutic sessions for BPD patients. Method: Using the FaceReader 7.0, 29 recordings of individual therapeutic sessions for BPD patients during an ACT intervention trial were analyzed. Results: Happiness and fear intensity increase from the beginning to the end of the sessions, while sadness decreases. Emotional valence exhibits a significant decrease in its negative value during sessions from −0.13 (S.D. = 0.12) at the initial part of the sessions to −0.06 (S.D. = 0.08) by the end of the sessions, with a moderate effect size (Cohen d = 0.69). Emotional arousal increased from the beginning to the end of sessions and whole intervention. Conclusion: The emotional valence and arousal differed according to the psychotherapeutically process involved during ACT intervention, suggesting that the systematic analysis of facial expressions allows a rigorously examination of the relations between emotions, physiological processes, and instrumental behavior experimented though a psychotherapeutically process.